Exploring Discursive Strategies of Dark Participation: User Comments on Migration in New York Times and Τhe Guardian - Spyridou, Lia Paschalia; Avraamidou, Maria (My University, 2023)
Digital media have multiplied the range of voices circulating in the public sphere(s), a terrain where journalists enjoyed special communication power. Despite optimism, research has offered mixed findings regarding the outcomes of participatory journalism assuming both constructive and negative interactions. This article draws from, and contributes, to a more nuanced exploration of “dark participation”, a concept broadly used to conceptualise online user contributions that are evil, tactical or strategic. Specifically, the article focuses on user comments in New York Times and the Guardian during the so-called 2015 “refugee crisis”. In addressing descriptive and exploratory research questions, it illustrates how dark participation can include disguised but equally strategic discursive strategies, like disclaimers and “half-truths” which may not always transgress the norms of civility but still tend to manipulate the conversation and normalise stereotyping and exclusion. Moreover, the study provides evidence associating antimigrant discourse with media attacks invoking radical right-wing populist narratives of “leftist” and “hypocritic” media operating as propaganda machines aiming to undermine the media’s integrity and neutralise their editorial position. The (intended) proliferation of antimigrant views and discourses associated with media attacks can be considered as a strategy to discourage inclusive and critical media reporting.
Keywords: Participatory journalism; Dark participation; Comments; Migration; Incivility; Discursive strategies